Macroporous poly(glycidyl methacrylate-co-ethylene glycol dimethacrylate) resins—Versatile immobilization supports for biocatalysts - Miletic, Nemanja; Vuković, Zorica; Nastasović, Aleksandra; Loos, Katja (Journal of Molecular Catalysis B: Enzymatic, 2009)
Crosslinked macroporous hydrophilic poly(glycidyl methacrylate-co-ethylene glycol dimethacrylate)s [abbreviated poly(GMA-co-EGDMA)] with identical chemical structure (60% of glycidyl methacrylate) but with varied average pore sizes (from 30 to 560 nm), specific surface areas (from 13.2 to 106.0 m2/g), specific volumes (from 0.755 to 1.191 cm3/g) and particle sizes (less than 100–650 microns) were synthesized via suspension polymerization. The influence of the resin properties on the loading of Candida antarctica lipase B (Cal-B) during immobilization and on the hydrolytic (hydrolysis of para-nitrophenyl acetate) and synthetic (ring-opening polymerization of -caprolactone) activity of the immobilized Cal-B were studied. Immobilization of Cal-B was performed at different temperatures and pH values. Cal-B immobilized at 30 ◦C and pH 6.8 was leading to increased activities. By decreasing the resin diameter: (i) the amount of Cal-B adsorbed onto the resin decreases, (ii) the conversion of para-nitrophenyl acetate increases (hydrolytic activity) and (iii) the conversion of e-caprolactone and the molecular weight of the synthesized poly-e-caprolactone increases (synthetic activity). Varying the porosity parameters results in different hydrolytic and synthetic activities. Pore sizes of all synthesized resins (from 30 to 560 nm) are big enough to overcome diffusion limitations. Therefore increasing the pore size of the resins resulted in a large increase in the hydrolytic and synthetic activity. Increasing the specific surface area resulted in an increase of activities, as the result of alleviated substrate approach to the immobilized enzyme zones. The obtained results were compared to results from dried Cal-B powder and Novozyme 435. Resin with particle size less than 100 microns and pore size 48 nm had much higher hydrolytic activity than both dried Cal-B powder and Novozyme 435. Nearly similar trends were observed for the synthetic activity. Via the DMSO leaching technique we could show that about 80% of Cal-B was ...